Methods for rapid prototyping novel labware: using CAD and desktop 3D printing in the microbiology laboratory. (1st December 2021) - Diep, T.T.; Ray, P.P.; Edwards, A.D.
Abstract: Although the microbiology laboratory paradigm has increasingly changed from manual to automated procedures, and from functional to molecular methods, traditional culture methods remain vital. Using inexpensive desktop fused filament fabrication 3D printing, we designed, produced and tested rapid prototypes of customised labware for microbial culture namely frames to make dip slides, inoculation loops, multi‐pin replicators, and multi‐well culture plates for solid medium. These customised components were used to plate out samples onto solid media in various formats, and we illustrate how they can be suitable for many microbiological methods such as minimum inhibitory concentration tests, or for directly detecting pathogens from mastitis samples, illustrating the flexibility of rapid‐prototyped culture consumable parts for streamlining microbiological methods. We describe the methodology needed for microbiologists to develop their own novel and unique tools, or to fabricate and customise existing consumables. A workflow is presented for designing and 3D printing labware and quickly producing easy‐to‐sterilise and re‐useable plastic parts of great utility in the microbiology laboratory. Abstract : Significance and Impact of the Study: We present methods for designing and 3D printing microbiological labware offering alternatives to off‐the‐shelf consumables that allow low‐cost rapid prototyping and customisation of microbial culture tools. We demonstrate customised 3D printed rapid prototype solid medium culture dishes and dip‐slides, and modified inoculating loops and customisable replicating pins for plating bacteria. 3D printed labware can offer local production to avoid dependence on commercial suppliers, rapid customisation of existing designs, and rapid evaluation of entirely new tools. Using 3D printing to develop novel labware tailored to simplify routine work in the microbiology laboratory can save time and labour compared to relying on off‐the‐shelf mass‐manufactured labware.